The exact status and synonyms of three Chinese Afronurus Lestage, 1924 established by Navás in 1936 (Ephemeroptera: Heptageniidae) - Ying, Xiaoli; Zhou, Changfa (Zootaxa, 2021)
Navás named more than 20 mayfly species from China but most of them are not associated with currently known specimens. In 2021, we found three common species of Chinese Afronurus Lestage, 1924 (Heptageniidae), which genitalia and color patterns match three species described and illustrated by Navás in 1936. Therefore, three new synonyms are established: Afronurus pallescens (Navás, 1936) (=Cinygmina obliquistriata You et al., 1981, syn. nov.), Afronurus kiangsuensis (Puthz, 1971) (renamed from Ecdyonurus hyalinus Navás, 1936= Cinygmina rubromaculata You et al., 1981, syn. nov.), Afronurus costatus (Navás, 1936) (=Cinygmina yixingensis Wu & You, 1986, syn. nov.). As the type specimens for Navas’ three species are supposed to be lost, neotypes are designated for them.